Texture changes of vegetable cultivars measured by non-destructive methods - Muha, V.; Istella, S. (International Journal of Horticultural Science, 2005)
According to our experiments the tested group of non-destructive methods offers a useful tool not only to follow the texture changes of vegetables during storage but to characterize the firmness and vision parameters during the growing period as well. Advantages of these methods are: they are mobile, easy to set up, easy to use and quick. The suitable maturity state — and so the optimum harvest date also - can be determined by these methods. In addition, these methods can be built into sorting lines making possible to sort and classify great amounts of produces. These methods help the producer to offer homogenous products of controlled quality. They can be used for measuring different effects on vegetable’s quality parameters (fertilization by different microelements, different irrigation effects on the product) as well.